Processing Verb Meanings and the Declarative/Procedural Model: A Developmental Study - Stefaniak, Nicolas; Baltazart, Véronique; Declercq, Christelle (Frontiers in Psychology, 2021)
According to the Declarative/Procedural Model, the lexicon depends on declarative memory while grammar relies on procedural memory. Furthermore, procedural memory underlies the sequential processing of language, especially cases that are probabilistic. Thus, this system is important for predicting the next item in a sentence. Verb processing represents a good candidate to test this assumption. Semantic representations of verbs include information about the protagonists in the situations they refer to. This semantic knowledge is acquired implicitly and used during verb processing, such that the processing of a verb preactivates its typical patients (e.g., the window for break). Thus, determining how the patient typicality effect appears during children’s cognitive development could provide evidence about the memory system that is dedicated to this effect. Two studies are presented in which French children aged 6 to 10 and adults made grammaticality judgments on 80 auditorily presented sentences. In Experiment 1, the verb was followed by a typical patient or by a less typical patient. In Experiment 2, grammatical sentences were constructed such that the verb was followed either by a typical patient or by a noun that could not be a patient of that verb. The typicality effect occurs in younger children and is interpreted in terms of developmental invariance. We suggest that this effect may depend on procedural memory, in line with studies that showed that meaning is necessary to allow procedural memory to learn the sequence of words in a sentence.